2020
DOI: 10.1002/ajpa.24075
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in daily activity intensity and energy expenditure and their relationship to cortisol among BaYaka foragers from the Congo Basin

Abstract: ObjectivesThe pooling of energetic resources and food sharing have been widely documented among hunter‐gatherer societies. Much less is known about how the energetic costs of daily activities are distributed across individuals in such groups, including between women and men. Moreover, the metabolic physiological correlates of those activities and costs are relatively understudied.Materials and methodsHere, we tracked physical activity, energy expenditure (EE), and cortisol production among Congo Basin BaYaka f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 75 publications
0
24
0
2
Order By: Relevance
“…Overall, women also exhibited less circadian fragmentation than men, and slightly stronger and more stable circadian rhythms. It is possible that, despite labor coordination between BaYaka men and women 20 , 35 , gender-differentiated work and social activities, particularly in the forest location, may drive gender differences in sleep expression and in circadian rhythms. Functional linear modelling analysis revealed that women had significantly higher activity levels than men, with a sharp rise in activity almost immediately after waking, which remained higher than men for the remainder of the day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, women also exhibited less circadian fragmentation than men, and slightly stronger and more stable circadian rhythms. It is possible that, despite labor coordination between BaYaka men and women 20 , 35 , gender-differentiated work and social activities, particularly in the forest location, may drive gender differences in sleep expression and in circadian rhythms. Functional linear modelling analysis revealed that women had significantly higher activity levels than men, with a sharp rise in activity almost immediately after waking, which remained higher than men for the remainder of the day.…”
Section: Discussionmentioning
confidence: 99%
“…This may be linked to collaboration in subsistence activities. For example, in the BaYaka community surveyed here, Sarma et al 35 found important complementarities in men and women’s work—BaYaka men and women will work side-by-side in gardens, with men clearing plots and women planting. Unlike other societies where heightened gender distinctions in types and intensities of subsistence roles drive significant differences in day and nighttime activity between men and women 36 , it is possible that BaYaka sleep patterns are similar between men and women because of a less rigid gendered division of labor.…”
Section: Introductionmentioning
confidence: 88%
“…shaping children's proper socialization; caring for ill children). As we have described in prior work, fathers' indirect care (Provider) was much more highly valued among the Bondongo, compared to direct caregiving (Direct), and Bondongo fathers engaged in relatively little direct care, on average 43,44 . In the current analyses we only included Bondongo rankings for Provider and Dispute, as they could be compared to similar domains among the BaYaka.…”
Section: Study Populationsmentioning
confidence: 56%
“…In the Bondongo sample, all participating fathers in the current analyses (n = 16) ranked one another using the same procedure we outlined above for the BaYaka rankings. The Cronbach's alphas for these peer-rankings were 0.84 (Dispute) and 0.95 (Provider) 44 . The Bondongo men in the sample knew each other well, as most had grown up together and/or were related through kinship by various degrees.…”
Section: Study Populationsmentioning
confidence: 96%
See 1 more Smart Citation